The Practice of Local Wisdom in Folklore as A Builder of the Early Conservation Spirit - Yayuk, Rissari; Jahdiah, Jahdiah; Riana, Derri Ris; Suryatin, Eka (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2023)
The future generation must have insight and practice local cultural knowledge in the era of globalization. The study aims to illustrate the representation of folklore as builders of the early cultural conservation spirit. The research data is an anthology of South Kalimantan folklore by H. Fahrurazie et al. UPT published by Taman Budaya Kalimantan Selatan in collaboration with Pustaka Banua publisher in 2013. The research method is qualitative descriptive—documentation and observation research techniques. The research steps are observation, determination of data sources, data collection, data selection, data analysis, conclusions, and presentation of data. The results showed that the representation of folklore has the practice of local wisdom, including a) knowledge of natural phenomena; b) practice in finding a source of life in the form of farming, gardening, and fishing; c) the practice of using living technologies and equipment; and d) practice of moral values in the literary arts. The conclusion is the source of insight and knowledge of wisdom, one of which is through folklore. Stakeholders, such as families, schools, and governments, play a role in providing oral and written literacy materials so that children get to know the culture early on.